Coincidence of Systemic Lupus Erythematosus and ANCA-Associated Vasculitis: A Case Report with Perforation of Nasal Septum and Palate - Liu Y; Yu S; Ma S; Yu J; Zuo D; Zhao W; Wang J; Wang J (Dove Medical Press, 2023)
Yurun Liu,1,* Shengnan Yu,2,* Sha Ma,2 Juan Yu,2 Dachen Zuo,2 Weiqing Zhao,2 Juan Wang,2 Jing Wang2 1Department of Rheumatology and Immunology, The Affiliated Hospital of Kunming University of Science and Technology, The First People's Hospital of Yunnan Province, Kunming, Yunnan, People's Republic of China; 2Department of Rheumatology and Immunology, The First People's Hospital of Yunnan Province, The Affiliated Hospital of Kunming University of Science and Technology, Kunming, Yunnan, People's Republic of China*These authors contributed equally to this workCorrespondence: Jing Wang, Department of Rheumatology and Immunology, The First People's Hospital of Yunnan Province, The Affiliated Hospital of Kunming University of Science and Technology, Kunming, Yunnan, People's Republic of China, Email wjing1981@163.comBackground: An overlap of systemic lupus erythematosus (SLE) and antineutrophil cytoplasmic antibodies- (ANCA-) associated vasculitis (AAV) is extremely uncommon and no clear definition has been proposed. The SLE/AAV overlap syndrome mainly affects kidney, blood count, nervous system and lung. However, few previous cases reported nasal septal and palatal perforation in this disorder.Case Presentation: We presented a case of a 16-year-old female with a 6-month history of SLE, developed perforation of the nasal septum and palate. She was diagnosed with SLE due to facial malar rash, oral ulcer, increased erythrocyte sedimentation rate (ESR), low complement levels, and positive anti-Smith antibody. Approximately 6 months later, she had a perforation of the nasal septum and palate with positive anti-proteinase 3 antibody (anti-PR3-ANCA). A nasal endoscopic biopsy revealed an inflammatory polyp with chronic suppurative inflammation and inflammatory granulomatous hyperplasia. In this case, the clinical, biological, radiological, and histological findings substantiated the diagnosis of AAV. Infections, drug abuse, malignancies, IgG4-related disease (IgG4-RD) and trauma were excluded. So we diagnosed her with SLE/AAV overlap syndrome.Conclusion: When a patient's symptoms cannot be explained by one disease, we need to consider the overlapping of two diseases, especially in patients with autoimmune diseases.Keywords: perforation of palate, systemic lupus erythematosus, ANCA-associated vasculitis, SLE/AAV overlap syndrome